THE SOLUBILITY OF IRIDIUM IN SILICATE MELTS: NEW DATA FROM EXPERIMENTS WITH IR10PT90 ALLOYS - Borisov A.; Palme H. (My University, 1995)
Solubilities of Ir in silicate melts of anorthite-diopside eutectic composition were determined by equilibrating IrPt-loops with silicates at a wide range of oxygen fugacities, from air to about 1.7 log units below the iron-wdstite buffer (IW-1.7) at 1300 and 1480°C. Instead of pure Ir metal, Ir10Pt90-alloys were used to avoid formation of tiny Ir nuggets in the silicate glass. Although nugget formation was less severe than in experiments with pure Ir metal, some samples were still contaminated as indicated by sporadically high Ir contents. These samples were subdivided and the separates were analysed again. Samples with high Ir were eliminated. The procedure was repeated several times until compositional uniformity of subsamples was achieved. In a log (Ir solubility) vs. log (FO2)-diagram the most reliable data plot along a line with a slope of about 14 suggesting Ir1+ as the formal Ir species in the melt, similar to earlier findings for Pd. The Ir solubility was found to be temperature independent within the range of temperatures used in the present experiments. The results with Ir10Pt90-alloys were recalculated to solubilities for pure Ir metal. These solubilities are significantly lower than earlier data (e.g., 1.52 ppb at IW-1 and 1478°C). As a result, calculated metal/silicate melt partition coefficients are extremely high (108−1012 at an oxygen fugacity corresponding to IW-2). Because of the uncertainty introduced by the presence of Ir nuggets it cannot be completely excluded that some of the solubility data are upper limits only. This would, however, only increase Ir metal/silicate partition coefficients and thus make arguments against a global core-mantle equilibrium stronger.